2021
DOI: 10.1371/journal.pone.0245859
|View full text |Cite
|
Sign up to set email alerts
|

Social media exposure, risk perception, preventive behaviors and attitudes during the COVID-19 epidemic in La Paz, Bolivia: A cross sectional study

Abstract: Social media has an important role in diffusion of information, during COVID-19 pandemic it could help to promote preventive behaviors, however its role and the pathway is still unclear. Objective To investigate the association among social media exposure, risk perception, preventive behaviors, and attitudes toward the COVID-19 epidemic in Bolivia. Methods We launched an online survey in La Paz and El Alto, Bolivia, during April and May 2020. The questionnaire examined: Socio-demographic factors, Social med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 27 publications
11
77
1
Order By: Relevance
“…Attitudes toward COVID-19 were also better among HCWs who got information from social media, followed by WHO websites. This is in line with a study that showed that social media exposure to COVID-19 information influences the adoption of preventive attitudes and behaviors through shaping risk perception [ 26 ]. Thus, understanding the role of social media during the pandemic could help policy makers and communicators to develop better communication strategies that enable HCWs to adopt appropriate attitudes and behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Attitudes toward COVID-19 were also better among HCWs who got information from social media, followed by WHO websites. This is in line with a study that showed that social media exposure to COVID-19 information influences the adoption of preventive attitudes and behaviors through shaping risk perception [ 26 ]. Thus, understanding the role of social media during the pandemic could help policy makers and communicators to develop better communication strategies that enable HCWs to adopt appropriate attitudes and behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…The reason for social media been the dominant sources of the vaccine messages is not farfetched bearing in mind the popularity of the social media for information dissemination in contemporary times. The study also collaborates with the study of Zeballos et al 44 which found that social media exposure to COVID-19 information influences the adoption of preventive attitudes and behaviors through shaping risk perception. This is in contrast with the study conducted by Al-Marshoudi et al 25 in Omani community's which found that their willingness to take COVID-19 vaccine can be enhanced by utilizing social media and community influencers to spread awareness about the vaccine's safety and efficacy.…”
Section: Discussionsupporting
confidence: 71%
“…The reason for social media been the dominant sources of the vaccine messages is not farfetched bearing in mind the popularity of the social media for information dissemination in contemporary times. The study also collaborates with the study of Zeballos et al 44 which found that social media exposure to COVID-19 information influences the adoption of preventive attitudes and behaviors through shaping risk perception.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We adapted this measure from previous studies (Choi et al, 2017;Oh et al, 2020;Rivas, 2021). Respondents were asked the question, "How often do you see information about COVID-19 when using social media like Facebook, Twitter, Blogs, or Youtube?"…”
Section: Social Media Exposurementioning
confidence: 99%